An innovative outpatient monitor service for gynecological patients in the United Kingdom: Case study evaluation of clinical effectiveness, economic outcomes, patient safety, and service improvement. (27th August 2021) - Tinelli, Michela; Jackson, Anne; Siddique, Sulman; Hamilton, Brian
Abstract: Background: Failure to attend appointments places a huge strain on health care systems around the world, resulting in poorer care for the patients, waste of staff time and increased waiting times. This study looked at the impact of an Outpatient‐Monitor‐Service (OMS) on clinical, economic, patient safety and service improvement outcomes in gynaecology patients compared with care as usual (with no access to the OMS). Methods: We conducted a retrospective match‐pair controlled study at a London‐based hospital. The cohort included adult women who received either (i) gynecological, (ii) hysteroscopy or (iii) vulval procedures. A cost‐consequences analysis compared intervention (who received the OMS) with control (historical cases who did not receive the OMS. Main outcome measures were clinical‐effectiveness, NHS‐cost, patient safety, and service improvement. Results: The intervention had positive impacts spanning clinical, patient safety and service improvement areas and showed cost saving results for the healthcare in terms of reduced follow‐up consultations and did‐not‐attend occurrences. Conclusions: The OMS offered by Message Dynamics appears to be a successful digital health technology to monitor gynecological patients' conditions and inform clinical decision making via remote channels, which is particularly relevant in coronavirus disease pandemic.